For Whom the Coin Tolls: Green Stained Teeth and Jaws In Medieval and Post-Medieval Spanish Burials - Kimberly A. Hopkinson; Sarah M. Yeats; G. Richard Scott (Dental Anthropology Association, 2008)
While observing dental characteristics in Spanish and Basque skeletons from the Cathedral of Santa Maria in Vitoria, Spain, an unusual pattern of staining was evident in 18 of 206 individuals. The stain, which permeated bone, dentine, calculus, and/or enamel, varied in color from bright green to turquoise. Males and females, all age categories, and medieval and post-medieval skeletons were equally affected. The green stain was the result of an ancient practice going back to Greek times that involved placing a silver or gold coin (obol) in the mouth of the deceased prior to burial for the purpose of paying the boatman (Charon) for passage across the river of woe (Acheron). In Spain, bronze coins substituted for silver and gold. The copper component of the bronze reacted with the acidic environment caused by decomposition creating basic copper carbonate. The copper carbonate then seeped into the porous spaces of the bones and teeth or replaced the mineral portion of the bone. The duration of this practice provides evidence that a seemingly 'pagan' ritual was preserved long after Christianity spread throughout Spain.